Small-Scale Fishing and Salmon Farming en Aysén. Itinerary of a Critical Investigation into Development in Southern Chile - Gonzalo Saavedra Gallo (CUHSO)
This study analyses the economic-cultural responses of twosmall-scale fishing villages of the Aysén coast in the face of the processesof economic development and modernisation currently occurring in theirterritory. The framework in which the problem is defined is the expansionof the caged salmon production industry, and the local promotionof the business mentality by State agencies. In general terms, these twofactors are observed in a process and in a wider spatial context in whichvarious actors coincide. We have called this space the field of development.Although the consequences of the process described —environmentaland territorial, socio-economic, socio-cultural and politico-cultural—may be associated with conventional perspectives, e.g. structural,or reflected in an objectivisation anchored in economic growth indicators,it is also significant to note the subjective aspects implied. We referin particular to the dynamics of practical structuring, which reveal other—unconventional— anthropological dimensions to the process. Underthis consideration we propose a horizontal hypothetical framework, inwhich we maintain that the decisive factors for economic developmentdo not emanate solely from public policy and/or the structuring and/ordestructuring forces of the market, since these capitalist modernisationprocesses are conditioned by dynamics of social and cultural structuringexpressed in the coastal-local development space.